2011
DOI: 10.1007/s00702-011-0668-8
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the antidepressants action: modulation of kynurenine pathway by increasing the kynurenic acid/3-hydroxykynurenine ratio

Abstract: Altered function of kynurenine pathway has emerged recently as one of the factors contributing to the pathogenesis of depression. Neuroprotective kynurenic acid (KYNA) and neurotoxic 3-hydroxykynurenine (3-HK) are two immediate metabolites of L: -kynurenine. Here, we aimed to assess the hypothesis that antidepressant drugs that may change brain KYNA/3-HK ratio. In primary astroglial cultures, fluoxetine, citalopram, amitriptyline and imipramine (1-10 μM) increased de novo production of KYNA and diminished 3-HK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 67 publications
7
38
0
Order By: Relevance
“…Regarding the a priori analyses, the ratios of KA/3HK and KA/QA, putative neuroprotective indices (Johansson et al, 2013;Kocki et al, 2012), were lower in the MDD group relative to the HCs (KA/3HK: t ¼ 2.42, p ¼ 0.019; KA/QA: t ¼ 2.04, p ¼ 0.047). However, after regressing out sex, age, and BMI, these differences no longer remained statistically significant (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the a priori analyses, the ratios of KA/3HK and KA/QA, putative neuroprotective indices (Johansson et al, 2013;Kocki et al, 2012), were lower in the MDD group relative to the HCs (KA/3HK: t ¼ 2.42, p ¼ 0.019; KA/QA: t ¼ 2.04, p ¼ 0.047). However, after regressing out sex, age, and BMI, these differences no longer remained statistically significant (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, psychiatric medication may increase the synthesis of the potentially neuroprotective compound, KA, and/or decrease the synthesis of 3HK. (Kocki et al (2012) reported that 24-48 h of exposure to selective serotonin reuptake inhibitors or tricyclic antidepressant medications stimulated the de novo synthesis of KA and decreased 3HK production in astroglial cultures, thus resulting in an increase in the KA to 3HK ratio. Patients with schizophrenia had lower plasma concentrations of KA and higher plasma concentrations of 3HK than HCs, an effect that was ameliorated by 6 weeks of treatment with antipsychotic treatment such that a significant increase in the KA/3HK ratio was observed after treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include anti-inflammatory treatments influencing immuno-inflammation such as cyclooxygensase-2 (COX-2) inhibitors, aspirin, minocycline and polyunsaturated fatty acids (Berk et al, 2013a, Fond et al, 2014, Muller, 2013 and antioxidant therapies to increase antioxidant defences and lower free radical damage such as n-acetyl cysteine, Ebselen, vitamin E and coenzyme-Q 10 (Berk et al, 2013b, Scapagnini et al, 2012. Interestingly, despite pharmaceutical antidepressants originally being heralded as targeting monoaminergic actions, there is also evidence that they can modulate immuno-inflammation, reduce oxidative stress, enhance neurotrophic factors and influence HPA activity (Abdel-Wahab and Salama, 2011, Andrade and Rao, 2010, Hannestad et al, 2011, Kocki et al, 2012, Schule, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…They have found no statistically significant increase in KYNA levels in the serum of patients after treatment with different antidepressants, relative to the pre-treatment baseline [3]. The results of an animal model study carried out by Kocki et al [33] indicate that citalopram, fluoxetine and amitriptyline increase the ratio of kynurenic acid to 3-hydroxykynurenine. These investigators [33] have found that these antidepressants modulate the kynurenine pathway, and that their effects may be associated with the restoration of the beneficial KYNA /3-OH-KYN ratio.…”
Section: Introductionmentioning
confidence: 95%